Analysis of the Use of Formalin as a Seafood Preservative by Traders at Mataram City Traditional Market - Asmawati, Asmawati; Ahmadi, Ahmadi; Saputrayadi, Adi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
?????????????????